2012
DOI: 10.5198/jtlu.v5i3.240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of light rail implementation on labor market accessibility: A transportation equity perspective

Abstract: This study seeks to examine transit's role in promoting social equity by assessing the before-after impacts of recent transit changes in the Twin Cities, including the opening of the Hiawatha light-rail line, on job accessibility among workers of different wage categories. Geospatial, descriptive, and regression analyses find that proximity to light-rail stations and bus stops offering direct rail connections are associated with large, statistically significant gains in accessibility to low-wage jobs. These ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 16 publications
0
86
0
Order By: Relevance
“…Other studies take into account the daily fluctuations of transit service by basing the accessibility measures on various departure times. Fan et al (2012) calculate travel time at every hour of the day and provide a daily accessibility based on average hourly travel times. and Lei and Church (2010) calculate the minimum travel time within a time window.…”
Section: Time-sensitive Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies take into account the daily fluctuations of transit service by basing the accessibility measures on various departure times. Fan et al (2012) calculate travel time at every hour of the day and provide a daily accessibility based on average hourly travel times. and Lei and Church (2010) calculate the minimum travel time within a time window.…”
Section: Time-sensitive Measuresmentioning
confidence: 99%
“…The research setting is the Greater Toronto Hamilton Area (GTHA). Building on previous studies (El-Geneidy et al, 2016;Fan et al, 2012;Legrain et al, 2015), we generate three accessibility measures for five daily time periods. The first accessibility measure is constant over the day, while the two other measures take into account the fluctuations in transit and job availability during the day.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that just as many studies show a positive outcome (Ong and Houston, 2002;Kawabata, 2002;Kawabata, 2003) as there which show small or ambiguous associations (Thakuriah and Metaxatos, 2000;Cervero, Sandoval and Landis, 2002;Bania, Leete and Coulton, 2008 The other is the study by Fan, Guthrie and Levinson (2010). They find that residential proximity to light rail stations and bus stops offering direct connection to rail stations are associated with statistically significant gains in accessibility to low-wage jobs (Fan, Guthrie and Levinson, 2010). In summary, there are very few studies showing the relationship between the provision of fixedguideway transit systems and higher levels of lower-wage jobs, and none evaluate this association with respect to BRT.…”
Section: Literaturementioning
confidence: 99%
“…Fan, Guthrie and Levinson (2010) provide an especially pertinent review of literature addressing our question. Citing Kain's (1968) pioneering work, they observe that the urban poor are harmed for want of affordable housing near job opportunities and reliable public transit to connect them to those jobs (Blumenberg, Ong and Mondschein, 2002;Sanchez, 2008).…”
Section: Literaturementioning
confidence: 99%
“…Fan et al (2012) calculated the number of jobs (per wage category) that can be reached within a 30-minute travel time from each residential block in the Minneapolis-Saint Paul area, both before and after the introduction of a new light-rail line. Comparing these figures for workers of different wage categories, they found that being located close to improved transit leads to large, statistically significant gains in accessibility for low-wage workers, and a positive equity impact.…”
Section: 2mentioning
confidence: 99%